FEMINISME ISLAM: KONTEKSTUALISASI PRINSIP-PRINSIP AJARAN ISLAM DALAM RELASI GENDER - Andri Rosadi (Universitas Islam Negeri Imam Bonjol Padang, 2011)
Gender issues come into being in Muslim world as a result of their interactions with modern western civilization through either colonialism or other ways. In addition to this external factor which can be regarded as triggering factor by which Muslim women’s awareness of their duties and rights started to emerge and develop, domination of men-biased interpretation of Islamic teachings also played an essential role in triggering the discours on gender issues. One of the responses to this issue is what so called Islamic feminism in Muslim world is a reaction to unjust but prevailing understanding and practice of Islamic teachings with regard to gender relation in favour of men. There are various issues related to this topic, but this article only contains the discussion on several Quranic verses regarding gender relation stating at the end that any interpretations of these verses is subject to change due to its profane nature. The principle is one: the core of Quranic spirit is equality. Finally, since the social fact of inequality of Muslim womens is very much influenced and shaped by men-biased interpretations, so Islamic Feminism is in fact more related to patriarchal value rather than divine one Keywords : Feminisme Islam, Kontekstualisasi prinsip ajaran Islam dan Relasi GenderCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i1.33